2016
DOI: 10.5194/angeo-34-857-2016
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale coordinated observations of Pc5 pulsation events

Abstract: Abstract. HF (high-frequency) radars belonging to SuperDARN (Super Dual Auroral Radar Network) receive backscatter over substantial fields of view which, when combined, allow for simultaneous returns over extensive regions of the polar caps and midlatitudes. This makes them ideal instruments for the observation of pulsations in the Pc5 (1-5 mHz) frequency band. Relatively few pulsation events observed by multiple radars have been reported in the literature. Here we describe observations of three such events wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In addition Mtumela et al. (2016) observed similar sunward‐propagating waves over a wide range (120°) of longitudes on the flanks of the magnetosphere. Thus the magnetometers used to detect these waves can be anywhere within a considerable range of magnetic local times before and after 06:00 and 18:00 MLT simultaneous with, or slightly later than, the TRINNI event in the tail.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…In addition Mtumela et al. (2016) observed similar sunward‐propagating waves over a wide range (120°) of longitudes on the flanks of the magnetosphere. Thus the magnetometers used to detect these waves can be anywhere within a considerable range of magnetic local times before and after 06:00 and 18:00 MLT simultaneous with, or slightly later than, the TRINNI event in the tail.…”
Section: Resultsmentioning
confidence: 87%
“…The analytic signal method of complex demodulation was applied to both magnetometer and CPCP data, so that the amplitude and phase of the signal at the frequency of the significant broadband ULF peak seen in both data sets could be accurately determined and compared. This complex demodulation method has been used previously with SuperDARN data to analyze ULF pulsations (Mtumela et al., 2016; Stephenson & Walker, 2010; Walker et al., 1992) and traveling ionospheric disturbances (Atilaw et al., 2021). It has also been employed widely for signal reconstruction in a variety of fields, in particular geomagnetic data (Banks, 1975), Pi2 pulsations (Beamish et al., 1979) and solar oscillations (Thomson et al., 1995).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The morphological properties of these types of ionospheric oscillations in the Pc5 band were very different from those of classical geomagnetic Pc5 waves. Mtumela et al (2016) found several Pc5-6 global events over an unusually large range of longitudes (>120°) on the afternoon/dusk side during very quiet geomagnetic conditions (Dst~0). In contrast to typical geomagnetic Pc5 waves, their sense of azimuthal phase propagation was westward (sunward) with the azimuthal wave number m~7-12.…”
Section: Discussionmentioning
confidence: 99%